The Importance of War Crimes Regulation in Indonesian Criminal Law - Fitri Arianti Saputri (PT. Anagata Sembagi Education, 2024)
Armed conflicts often involve violations of humanitarian law and the laws of war, causing adverse impacts on civil society. The involvement of states in international conflicts drives the need for comprehensive war crimes regulation to uphold humanitarian values and protect human rights. In the context of the Israeli-Palestinian conflict, the role of the UN as a global organization becomes crucial, and Indonesia, as a UN member state, has a responsibility to contribute to achieving peace and maintaining world order. Although Indonesia has Law No. 26/2000 on Human Rights Courts, the regulation does not explicitly cover war crimes as stipulated in the 1998 Rome Statute. The history of war law in Indonesia shows the need for reform to accommodate more modern principles of international law. The push for the establishment of more comprehensive regulations related to international humanitarian law shows the international world's awareness of the need to regulate international crimes more clearly and firmly. Support from various parties, including civil society, scientists, NGOs and the government, is key in ensuring the realization of effective and equitable regulations related to war crimes in Indonesia. Indonesia needs to respond seriously to the urgency of establishing war crimes regulations to make a positive contribution to maintaining global peace, protecting human rights, and bringing justice to victims of war crimes.